Giving names to features in geology; the choice between subjective listing or researching objective natural divisions - Lunt, Peter; Luan, Xiwu (Berita Sedimentologi, 2023)
In literature the English playwright Shakespeare proposed that “a rose by any other name would smell as sweet”. Many geologist are also flexible about the names they apply to features, and are tolerant of both over-simplification and even making mistakes in the naming of formations or other features. It appears that precision of a single noun is considered subservient to the essence of the narrative, such as evaluating a hydrocarbon prospect, or giving an interpretation of history. Here it is argued that naming is important because geology is so rich in nouns, and consequently compound errors in the use of multiple, poorly-defined nouns rapidly degrades overall meaning. It is proposed that without names that are both natural and consistently applied, but also continually improved, the scientific framework soon falls apart. By this we mean that the geological understanding of exploration risk, or geological history, rapidly become too easily accommodating of any new data and thus loses all rigour. Good, natural names are the results of tested concepts and are themselves open to further testing. From such testing comes recognition that in nature there are both gradational variation in series as well as discrete categories. A search for good names is inexorably linked to a better understanding of the features concerned.